A 1200-year multiproxy record of tree growth and summer temperature at the northern pine forest limit of Europe - McCarroll, D.; Loader, N.J.; Jalkanen, R.; Gagen, M.H.; Grudd, H.; Gunnarson, B.E.; Kirchhefer, A.J.; Friedrich, M.; Linderholm, H.W.; Lindholm, M.; Boettger, Tatjana; Los, S.O.; et al. (The Holocene, 2013)
Combining nine tree growth proxies from four sites, from the west coast of Norway to the Kola Peninsula of NW Russia, provides a well replicated (> 100 annual measurements per year) mean index of tree growth over the last 1200 years that represents the growth of much of the northern pine timberline forests of northern Fennoscandia. The simple mean of the nine series, z-scored over their common period, correlates strongly with mean June to August temperature averaged over this region (r = 0.81), allowing reconstructions of summer temperature based on regression and variance scaling. The reconstructions correlate significantly with gridded summer temperatures across the whole of Fennoscandia, extending north across Svalbardand south into Denmark. Uncertainty in the reconstructions is estimated by combining the uncertainty in mean tree growth with the uncertainty in the regression models. Over the last seven centuries the uncertainty is < 4.5% higher than in the 20th century, and reaches a maximum of 12% above recent levels during the 10th century. The results suggest that the 20th century was the warmest of the last 1200 years, but that it was not significantly different from the 11th century. The coldest century was the 17th. The impact of volcanic eruptions is clear, and a delayed recovery from pairs or multiple eruptions suggests the presence of some positive feedback mechanism. There is no clear and consistent link between northern Fennoscandian summertemperatures and solar forcing.